2014
DOI: 10.1080/15374416.2014.886252
|View full text |Cite
|
Sign up to set email alerts
|

Callous-Unemotional Behavior and Early-Childhood Onset of Behavior Problems: The Role of Parental Harshness and Warmth

Abstract: Objective Youth with callous unemotional (CU) behavior are at risk of developing more severe forms of aggressive and antisocial behavior. Previous cross-sectional studies suggest that associations between parenting and conduct problems are less strong when children or adolescents have high levels of CU behavior, implying lower malleability of behavior compared to low-CU children. The current study extends previous findings by examining the moderating role of CU behavior on associations between parenting and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 49 publications
3
45
0
Order By: Relevance
“…In these analyses, we found that observed parental harshness was related to increases in child CU behavior from ages 2–4, over and above earlier behavior problems and relevant covariates (Waller, Gardner, Hyde, et al, 2012). Next, using both self-reported parental warmth and two observed measures of parental warmth (assessed via global coding of parent-child interactions in the family home and coding of parental five-minute speech samples; Waller, Gardner, Dishion et al, 2012), we found that parental warmth and CU behavior were reciprocally related from ages 2–3, even taking into account shared method variance across parental reports of higher behavior problems and their parental warmth at both ages 2 and 3 (Waller, Gardner, et al, 2015; Waller, Gardner et al, 2014). Specifically, early parent-reported CU behavior in toddlers predicted fewer observed displays of parental warmth over time, while lower parental warmth simultaneously and uniquely predicted increases in child CU behavior, controlling for earlier and concurrent behavior problems (Waller, Gardner et al, 2014).…”
Section: Are Parenting Practices Associated With the Development Of Cmentioning
confidence: 92%
See 1 more Smart Citation
“…In these analyses, we found that observed parental harshness was related to increases in child CU behavior from ages 2–4, over and above earlier behavior problems and relevant covariates (Waller, Gardner, Hyde, et al, 2012). Next, using both self-reported parental warmth and two observed measures of parental warmth (assessed via global coding of parent-child interactions in the family home and coding of parental five-minute speech samples; Waller, Gardner, Dishion et al, 2012), we found that parental warmth and CU behavior were reciprocally related from ages 2–3, even taking into account shared method variance across parental reports of higher behavior problems and their parental warmth at both ages 2 and 3 (Waller, Gardner, et al, 2015; Waller, Gardner et al, 2014). Specifically, early parent-reported CU behavior in toddlers predicted fewer observed displays of parental warmth over time, while lower parental warmth simultaneously and uniquely predicted increases in child CU behavior, controlling for earlier and concurrent behavior problems (Waller, Gardner et al, 2014).…”
Section: Are Parenting Practices Associated With the Development Of Cmentioning
confidence: 92%
“…We focused on observations of positive reinforcement to be consistent with our previous work examining associations between positive affective aspects of parenting (e.g., warmth, praise) and child CU behavior (see Waller, Gardner et al, 2015; Waller, Gardner et al, 2014). Positive reinforcement was assessed at 27-months via microsocial coding of a 3-minute clean-up task, during which parents had to guide the child to put toys away, based on codes derived from the Child Free Play and Compliance Task Coding Manual (Pears & Ayers, 2000).…”
Section: Applying Models Of Cu Behavior Within An Adoption Designmentioning
confidence: 98%
“…For example, CU traits have been reliably associated with caregiving experiences (Pardini, Lochman, & Powell, 2007;Waller et al, 2012); furthermore, not all studies find that the associations between parenting and child behavioral adjustment are moderated by CU, e.g. (Waller et al, 2014), or that CU traits moderate treatment response to intervention (Kolko & Pardini, 2010). More notable contrary findings include the observation that caregiving quality predicts CU stability (P. J.…”
Section: Observational and Experimental Findingsmentioning
confidence: 99%
“…Overall, developmental theories have identified parents’ harsh discipline and warmth as key factors involved in the development and prevention of conduct problems and other antisocial-related outcomes. Although some prior studies have found significant associations between these parenting dimensions in early and middle childhood (e.g., Kroneman, Hipwell, Loeber, Koot, & Pardini, 2011; Waller et al, 2015a), there is reason to believe that they may have non-overlapping influences on developmental outcomes.…”
mentioning
confidence: 98%